Sosialisasi Pajak sebagai Moderasi Pengaruh Literasi Pajak dan Digitalisasi Pajak terhadap Kepatuhan Wajib Pajak - Aini, Aida; Erna Chotidjah Suhatmi; Ety Meikhati (Jurnal Bisnis Manajemen dan Akuntansi (BISMAK), 2025)
The decline in Indonesia’s tax ratio 2022–2024 reflects that overall tax compliance has yet to reach an optimal level. In contrast, KPP Pratama Surakarta recorded tax revenues surpassing the set targets within the same period, indicating relatively strong taxpayer compliance in its jurisdiction. This study seeks to examine the moderating effect of tax socialization on the relationship between tax literacy, tax digitalization, and taxpayer compliance. The research population consists of individual taxpayers registered at KPP Pratama Surakarta, with 100 respondents selected as the sample. A quantitative research design was applied, utilizing primary data collected through questionnaires, and the analysis was conducted using SPSS version 26. The findings demonstrate that tax literacy, tax digitalization, and tax socialization each have a significant impact on taxpayer compliance. Moreover, tax socialization is found to strengthen the effect of tax literacy on compliance, while its moderating role is not evident in the relationship between tax digitalization and taxpayer compliance.